A Crank-Nicolson scheme: $$ \begin{align*} \frac{S^{n+1}-S^n}{\Delta t} &= -\beta [SI]^{n+\half} \approx -\frac{\beta}{2}(S^nI^n + S^{n+1}I^{n+1})\\ \frac{I^{n+1}-I^n}{\Delta t} &= \beta [SI]^{n+\half} - \nu I^{n+\half} \approx \frac{\beta}{2}(S^nI^n + S^{n+1}I^{n+1}) - \frac{\nu}{2}(I^n + I^{n+1}) \end{align*} $$
New notation: \( S \) for \( S^{n+1} \), \( S^{(1)} \) for \( S^n \), \( I \) for \( I^{n+1} \), \( I^{(1)} \) for \( I^n \) $$ \begin{align*} F_S(S,I) &= S - S^{(1)} + \half\Delta t\beta(S^{(1)}I^{(1)} + SI) = 0\\ F_I(S,I) &= I - I^{(1)} - \half\Delta t\beta(S^{(1)}I^{(1)} + SI) - \half\Delta t\nu(I^{(1)} + I) =0 \end{align*} $$